THE USE OF TELEGRAM TO IMPROVE STUDENTS' VOCABULARY - Irsyad Izzul Haq; Chairil Anwar Korompot; Nur Aeni (JTechLP: Journal of Technology in Language Pedagogy, 2022)
The purpose of this study was to determine whether or not Telegram was useful for teaching vocabulary. The researchers employed a pre-experimental design with a single group for the pre-test, post-test, and vocabulary quiz. In the academic year 2022–2023, the population consisted of Muhammadiyah Tanetea 8th-grades. The sample, which included 14 students, was drawn using the cluster random sampling technique. A vocabulary test was given as a pre-test, post-test, and vocabulary quiz. The result of this research proved that there was a significant difference between students’ scores before treatment and students’ scores after treatment. It can be seen from the mean score, the mean score of students’ pre-tests (56.21), was lower than the mean score of the post-tests (72.21). The significant value of this research (0.000) was smaller than the significant level (0.05). It can be concluded that the use of Telegram can improve students’ vocabulary mastery of the 8th-grade students of MTs Muhammadiyah Tanetea.